2020
DOI: 10.1002/ese3.768
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element simulation for investigating fragmentation mechanism of hard rock under ultrasonic vibration loading

Abstract: With the gradual depletion of shallow resources, the energy exploration depth has been increasing and condition becomes complex. 1 Consequently, the explorations face increasingly harder rocks with higher strengths. Breaking hard rock rapidly in petroleum and mineral exploration is a popular and significant topic. 2-6 However, the current technologies cannot meet the demands of quick drilling. It is necessary to develop a more efficient technology for hard rock exploration. To achieve this goal, the assisted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Tang Yang et al designed a straight rotating mixing nozzle [18]. Tang Qiongqiong et al presented a rockcrushing mechanism that used ultrasonic vibration through numerical simulation and experimental research [19]. Rock-breaking efficiency can be improved by using ultrasonic vibration technology.…”
Section: Introductionmentioning
confidence: 99%
“…Tang Yang et al designed a straight rotating mixing nozzle [18]. Tang Qiongqiong et al presented a rockcrushing mechanism that used ultrasonic vibration through numerical simulation and experimental research [19]. Rock-breaking efficiency can be improved by using ultrasonic vibration technology.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic vibration is a type of cyclic loading action at ultrahigh frequencies that is capable of generating the same or similar frequencies as the inherent frequency of hard rock [17]. Under the infuence of certain high-frequency cyclic loads, the rock resonates, with fatigue damage occurring inside it [18]. Zhao et al [19] used nondestructive thermal imaging technology to monitor the temperature climbing phenomenon of rocks before damage under ultrasonic vibration loads and concluded that the causal factors of rock damage are fatigue damage and thermal damage produced by alternating loads on rocks.…”
Section: Introductionmentioning
confidence: 99%